2013
DOI: 10.1016/j.cmet.2013.06.013
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-wide Association Study of the Human Metabolome in a Community-Based Cohort

Abstract: SUMMARY Because metabolites are hypothesized to play key roles as markers and effectors of cardio-metabolic diseases, recent studies have sought to annotate the genetic determinants of circulating metabolite levels. We report a genome-wide association study (GWAS) of 217 plasma metabolites, including >100 not measured in prior GWAS, in 2,076 participants of the Framingham Heart Study. For the majority of analytes, we find that estimated heritability explains >20% of inter-individual variation, and that variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
279
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 290 publications
(294 citation statements)
references
References 73 publications
10
279
2
3
Order By: Relevance
“…At both 2 and 6 months after RYGB, patients had dramatic weight loss and also significant improvements in metabolic parameters, such as glucose levels, systolic blood pressure ate, ADMA, and alanine (25). Our group and others have previously reported associations between common variants in the AGXT2 gene with circulating metabolite levels in human blood (17,20,32) and urine (17). Our data therefore extend the findings of previous studies by demonstrating that DMGV is a bona fide product of AGXT2 metabolism in humans.…”
Section: Confirmation Of Dmgv As the Correct Identity Of M/z 2021185supporting
confidence: 78%
See 3 more Smart Citations
“…At both 2 and 6 months after RYGB, patients had dramatic weight loss and also significant improvements in metabolic parameters, such as glucose levels, systolic blood pressure ate, ADMA, and alanine (25). Our group and others have previously reported associations between common variants in the AGXT2 gene with circulating metabolite levels in human blood (17,20,32) and urine (17). Our data therefore extend the findings of previous studies by demonstrating that DMGV is a bona fide product of AGXT2 metabolism in humans.…”
Section: Confirmation Of Dmgv As the Correct Identity Of M/z 2021185supporting
confidence: 78%
“…However, comparison of MS/MS fragmentation of multiple authentic reported a GWAS of 217 plasma metabolite traits measured in 2,076 participants of the Framingham Heart Study (FHS). Further, and as corroborated by other published metabolite GWAS, many of the strongest associations we identified were at loci that encode transporters or enzymes with a direct biochemical relationship with the metabolite (20,21). Therefore, we hypothesized that in the context of nontargeted profiling, a genetic association with an unknown metabolite could aid in its identification by highlighting a specific enzymatic reaction.…”
Section: Introductionmentioning
confidence: 50%
See 2 more Smart Citations
“…Because these reactions are performed by various enzymes, PFAA profiles may be influenced by genetic variations in enzymes involved in AA metabolism. In fact, a prior genome‐wide association study (GWAS) of the human metabolome indicated that certain AAs are associated with genetic loci encoding either AA transporters or enzymes involved in serine (Ser) biosynthesis (Rhee et al, 2013). …”
mentioning
confidence: 99%